2021
DOI: 10.1111/jvim.16040
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a point‐of‐care test using voided urine samples for detection of bacteriuria in dogs with signs of lower urinary tract disease

Abstract: Background: Bacterial urine culture is recommended in dogs suspected of having urinary tract infection (UTI), but there is expense and delay in obtaining such results. Hypothesis/Objective: To determine the diagnostic performance of a rapid immunoassay (RIA) dipstick for detection of bacteriuria using voided urine from dogs with clinical signs of lower UTI. Animals: Twenty-four client-owned dogs. Methods: Voided urine was collected and the RIA performed within 30 minutes. Urine collected by cystocentesis was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
2
11
1
Order By: Relevance
“…The 90.0% sensitivity and 95.2% specificity for the RIA in our study are likely similar to previous publications (97.4% sensitivity and 98.8% specificity) for urine cultures with growth ≥10 3 CFU/mL, and for voided specimens in dogs with LUTS (89% sensitivity and 100% specificity) 6,10 . While confidence intervals in our study were larger than anticipated for evaluation of the sensitivity of this test, they were narrower than those reported by Grant et al 6 No confidence intervals were provided for the other study for comparison 10 . Jacob et al 10 scored and photographed all results and data were interpreted by 1 investigator, our study mimics how the test would be performed in most veterinary practices where the result would be interpreted at the point‐of‐care.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The 90.0% sensitivity and 95.2% specificity for the RIA in our study are likely similar to previous publications (97.4% sensitivity and 98.8% specificity) for urine cultures with growth ≥10 3 CFU/mL, and for voided specimens in dogs with LUTS (89% sensitivity and 100% specificity) 6,10 . While confidence intervals in our study were larger than anticipated for evaluation of the sensitivity of this test, they were narrower than those reported by Grant et al 6 No confidence intervals were provided for the other study for comparison 10 . Jacob et al 10 scored and photographed all results and data were interpreted by 1 investigator, our study mimics how the test would be performed in most veterinary practices where the result would be interpreted at the point‐of‐care.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of positive urine cultures in our study (45% ≥ 10 3 CFU/mL) was higher than that reported in studies that either evaluated this RIA or other point‐of‐care assays 6,10,15,16 . This can be attributed to our inclusion criteria, which selected for dogs that were more likely to have bacteriuria.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Diagnostic tests may perform differently if limited to a particular population, for example, only those with clinical signs of UTI [ 10 , 11 ]. UTid+, as with all diagnostic tests, should always be interpreted in the context of the clinical patient and should only form part of the clinical decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment analysis, as part of urinalysis, may be used to identify bacteriuria at POC but interpretation likely depends on the skill of the evaluator and has been shown to have low sensitivity [ 9 ]. Other POC tests such as a rapid immunoassay, a urine catalase test, a urine dipstick paddle culture system, and compartmented bacterial culture plates have been evaluated for use in companion animal veterinary medicine and demonstrate variable accuracy [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%